Investigação dos mecanismos de ação do ácido ɑ-lipóico em um modelo animal de mania induzida por anfetamina - Medeiros, Camila Dantas (2013)
Bipolar disorder (BD) is a chronic disorder, prevalent and associated with increased risk of suicide. The pathophysiology of BD remains uncertain. Several studies point to the involvement of oxidative stress in its neurobiology. The α-lipoic acid (AAL) has been tested in several pathologies of the central nervous system once it has different antioxidant activities, such as: metal chelator, regenerating endogenous antioxidants and neutralizing reactive oxygen species. The AAL showed effectiveness and safety in various preclinical and clinical studies with diseases associated with oxidative damage, such as diabetic neuropathy and ischemia-reperfusion. One of the animal models of acute mania that is best characterized nowadays is the locomotor hyperactivity induced by d-amphetamine (d-ANF). Previous studies show that mood stabilizers such as lithium and valproate can reverse and prevent the increase in locomotor activity induced by d-ANF. Many evidences show that BD is associated with increased oxidative stress. As AAL has antioxidant activity and had not been studied in BD yet, the present study aimed to test the effects of AAL in the reversal and prevention of mania induced by d-ANF in mice. In the reversal protocol, adult mice first received d- amphetamine (d-ANF) 2mg/kg intraperitoneally (i.p.) or saline for 14 days. Between day 8 and 14 animals received AAL 50 or 100 mg / kg orally, lithium (Li) 47.5 mg / kg i.p. or saline. In the prevention protocol, mice were pretreated with AAL, Li or saline before administration of d-ANF. The locomotor activity was assessed using the open field behavioral test. The activity of superoxide dismutase (SOD), the levels of reduced glutathione (GSH) and thiobarbituric acid reactive substance (TBARS) were evaluated in the prefrontal cortex (CPF), hippocampus (HC) and striatum (CE). In addition, the levels of brain-derived neurotrophic factor (BDNF) were measured in the HC. AAL and Li prevented and reversed the increase in locomotor activity induced by d-ANF. In the prevention model, the AAL and Li when co- administered with d-ANF prevented the increase of SOD activity induced by d-ANF in HC and CE, respectively; AAL and Li prevented the alteration of GSH levels in HC and TBARS formation in all brain areas investigated. In the reversal model, AAL reversed the decrease in SOD activity in CE. The formation of TBARS was reversed by AAL and Li in all brain areas mentioned. Additionally, AAL reversed the decreased levels of BDNF and GSH in HC. Conclusively, the results showed that the AAL, similarly to Li, is effective in reversing and preventing behavioral and neurochemical changes induced by d-ANF, providing the basis for the development of clinical trials to investigate the AAL’s possible antimanic effects.